Peran Halal Awareness dan Brand Image Terhadap Keputusan Pembelian Produk Richeese Factory dengan Minat Beli Sebagai Variabel Intervening: Studi pada Konsumen Richeese Factory di Yogyakarta - Putri Alifka Muchtiara; Murry Harmawan Saputra; Hubi Rahmat Andika (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of halal awareness and brand image on purchase decisions through purchase intention as an intervening variable among Generation Z consumers of Richeese Factory in Yogyakarta. The research employed a quantitative approach with a survey method. Data were collected through an online questionnaire distributed to consumers who had previously purchased products from Richeese Factory in Yogyakarta. The sampling technique used was purposive sampling, resulting in 150 respondents. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.1.1 software. The results indicate that halal awareness has a positive and significant effect on purchase decisions and purchase intention. Brand image also has a positive and significant effect on purchase decisions and purchase intention. Furthermore, purchase intention has a positive and significant effect on purchase decisions. The mediation analysis reveals that purchase intention successfully mediates the relationship between halal awareness and purchase decisions, as well as the relationship between brand image and purchase decisions. These findings suggest that consumers' awareness of halal aspects and positive perceptions of a brand play important roles in increasing purchase intention, which subsequently encourages purchase decisions. This study contributes to the development of consumer behavior literature, particularly in the halal food industry, and provides practical implications for companies in strengthening halal awareness and brand image to improve consumers' purchase decisions.